2016
DOI: 10.1021/acs.energyfuels.6b02253
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Gelation Process and Gel Structure of Water-in-Waxy Crude Oil Emulsion

Abstract: The W/O emulsion formed by waxy crude oil tends to gelatinize under low-temperature gathering conditions, which may harm the flow assurance of multiphase transportation. This study mainly focused on the wax-precipitating gelation process of crude oil emulsions, and the structural differences of the emulsions with different water fractions at their gelation temperatures (GTs). First, the changes of wax appearance temperature (WAT) and precipitated wax amount at GT with variable water cut were investigated by DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Wang et al investigated the effect of water content in waxy crude oil emulsion on the gelation behavior and found that the gelation behavior of waxy crude oil is enhanced with the addition of water. A similar observation (i.e., increase in gelation temperature with an increase in water cut) was also made in previous studies. , Ekweribe et al investigated the effects of system pressure on the gelation and the yielding process using a controlled stress rheometer (CSR) and a model pipeline system. They observed that gelation temperature increases with an increase in system pressure.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Wang et al investigated the effect of water content in waxy crude oil emulsion on the gelation behavior and found that the gelation behavior of waxy crude oil is enhanced with the addition of water. A similar observation (i.e., increase in gelation temperature with an increase in water cut) was also made in previous studies. , Ekweribe et al investigated the effects of system pressure on the gelation and the yielding process using a controlled stress rheometer (CSR) and a model pipeline system. They observed that gelation temperature increases with an increase in system pressure.…”
Section: Introductionsupporting
confidence: 67%
“…A similar observation (i.e., increase in gelation temperature with an increase in water cut) was also made in previous studies. 12,35 Ekweribe et al 36 investigated the effects of system pressure on the gelation and the yielding process using a controlled stress rheometer (CSR) and a model pipeline system. They observed that gelation temperature increases with an increase in system pressure.…”
Section: Introductionmentioning
confidence: 99%
“…As is shown in Figure , the paraffinic wax in crude oil A begins to precipitate at about 54.3 °C, and in crude oil B at about 34.2 °C. Although the WATs of the crude oils will be slightly increased after emulsification according to our previous test and the test result of Piroozian et al, it brings no difference to the conclusion. Below these temperatures, the precipitated wax crystals can attract each other and gradually form a three-dimensional network structure in the oil phase, and they can also entrap the droplets in W/O emulsions by adsorbing at the oil/water interface .…”
Section: Resultssupporting
confidence: 62%
“…Among the physical parameters, the density was obtained according to ASTM D1298-2012b, the pour point was measured based on ASTM D5853-11, and the contents of the four fractions were measured in accordance with ASTM D4124-09. The wax appearance temperature (WAT) was tested with a differential scanning calorimeter (DSC-821 e , Mettler-Toledo, Switzerland), and the wax content was calculated according to the common method in the literature. , Water phase: To simulate the formation water, the water phase was prepared with distilled water and sodium chloride. The concentration of sodium chloride in the brine water was controlled at 0.05 mol/L. Dissolved CO 2 : The CO 2 gas used in the experiments was obtained from Airtechina Co., Ltd. Its purity was above 99.9%. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation